Genetic Relationships of Indigenous King Coconut (Cocos nucifera L.) Populations as Determined by SSR Markers - Meegahakumbura, Muditha Kasun; Indrachapa, M. T. N.; Baddegama, T. S.; Hettiarachchi, M. M.; Dissanayaka, H. D. M. A. C.; Samarasinghe, C. R. K.; Weerasinghe, P. R.; Dasanayake, P. N. (International Coconut Community Journal, 2023)
King Coconut (KC) is an indigenous and highly valuable germplasm resource in Sri Lanka. Yet, KC populations' genetic diversity, relationships, and conservation strategies are not fully understood. Indigenous old KC populations have been dispersed across a few ancient villages in Sri Lanka. Five geographically dispersed locations were selected in Sri Lanka, and 20 KC individuals from each location were collected for the current study. Six randomly selected samples from every geographical location, together with the standard two Sri Lanka Red Dwarf and two Sri Lanka Tall varieties were initially genotyped using 21 SSR markers for polymorphism. Based on the results, ten polymorphic SSR markers were selected and used for genotyping. Power Marker, STRUCTURE, and GenAlex software were used for the SSR genetic analysis. Results revealed 0.62 mean Gene Diversity (Hs), 4.2 mean allele number, and 0.55 polymorphic information content (PIC). Clear differentiation of populations was observed with the STRUCTURE and UPGMA dendrogram. Single branching in the UPGMA dendrogram for Anuradhapura and Marandawila KC populations revealed high genetic uniformity over multi-branched Kadugannawa and Colambageara populations. According to AMOVA, 64% of the genetic variation has been partitioned among populations, indicating moderate population differentiation. Detail analysis, including a higher number of KC populations and systematic molecular analysis using more SSRs/SNPs needed in the future before implementing conservation and utilization strategies.